2020
DOI: 10.24310/riccafd.2020.v9i1.8307
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje-servicio en educación física: un modelo de implementación en educación superior

Abstract: La finalidad de esta propuesta es presentar un modelo de implementación de la metodología docente de Aprendizaje-servicio (ApS) para favorecer la formación de estudiantes del grado universitario de Educación Primaria en la Facultad de Psicología, Ciencias de la Educación y del Deporte (FPCEE) Blanquerna, Universidad Ramon Llull (URL). Se muestra el procedimiento ApS así como su conveniencia para favorecer competencias docentes relacionadas con habilidades de aprendizaje, como trabajo en equipo o innovación, y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In the same vein, Marttinen et al [ 11 ], Galván et al [ 46 ], and Du Toit [ 44 ] concluded that the SL program improved students’ pedagogical knowledge and professional skills. Franco-Solà and Figueras [ 45 ] assessed teaching skills using the Framework for 21st Century Learning and found that SL helped to improve cognitive, emotional, and social competences among PETE students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, Marttinen et al [ 11 ], Galván et al [ 46 ], and Du Toit [ 44 ] concluded that the SL program improved students’ pedagogical knowledge and professional skills. Franco-Solà and Figueras [ 45 ] assessed teaching skills using the Framework for 21st Century Learning and found that SL helped to improve cognitive, emotional, and social competences among PETE students.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies assessed the acquisition of professional skills from SL with specific populations (17/31) such as cognitively impaired individuals [ 52 , 55 ], children with disabilities special educational needs [ 27 , 34 , 38 , 39 , 43 , 45 , 59 ] children with attention deficit hyperactivity disorder [ 51 ], others diversity as cultural dimension, low SES schools, disadvantaged population, minority groups [ 10 , 11 , 35 , 42 , 47 , 52 ] and older adults [ 54 , 58 ]. Surprisingly, Willard and Crandall [ 58 ] found no increase in students’ knowledge of PA and attitudes towards PA with older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Contextos Educ., 27 (2021), 65-81 En la FPCEEB han sido diversas las experiencias llevadas a cabo en los últimos años en el campo de la actividad física, deporte y EF (Arboix et al, 2013;Arranz et al, 2013;Escofet y Fuertes, 2018;Franco-Sola y Figueras, 2020;Rubio, Campo y Sebastiani, 2014;Sebastiani y Campos, 2017;Sebastiani et al, 2012).…”
Section: Introductionunclassified